2012
DOI: 10.1128/jvi.06549-11
|View full text |Cite
|
Sign up to set email alerts
|

West Nile Virus Infections Suppress Early Viral RNA Synthesis and Avoid Inducing the Cell Stress Granule Response

Abstract: West Nile virus (WNV) recently became endemic in the United States and is a significant cause of human morbidity and mortality. Natural WNV strain infections do not induce stress granules (SGs), while W956IC (a lineage 2/1 chimeric WNV infectious clone) virus infections produce high levels of early viral RNA and efficiently induce SGs through protein kinase R (PKR) activation. Additional WNV chimeric viruses made by replacing one or more W956IC genes with the lineage 1 Eg101 equivalent in the W956IC backbone w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
65
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 57 publications
8
65
0
Order By: Relevance
“…PKR is activated by dsRNA produced during flavivirus RNA replication. Protection of viral RNA by intracellular membrane structures away from the host RNA sensors may be one mechanism to downregulate PKR activation, as reported for WNV infection (13). However, IFN-␤ gene expression, which is turned on by intracellular sensing of viral RNA, could be detected as early as 4 to 8 h after JEV infection (8); other mechanisms besides hiding viral RNA inside membrane structures, might also respond for PKR suppression during early stage of JEV infection.…”
Section: Discussionmentioning
confidence: 84%
“…PKR is activated by dsRNA produced during flavivirus RNA replication. Protection of viral RNA by intracellular membrane structures away from the host RNA sensors may be one mechanism to downregulate PKR activation, as reported for WNV infection (13). However, IFN-␤ gene expression, which is turned on by intracellular sensing of viral RNA, could be detected as early as 4 to 8 h after JEV infection (8); other mechanisms besides hiding viral RNA inside membrane structures, might also respond for PKR suppression during early stage of JEV infection.…”
Section: Discussionmentioning
confidence: 84%
“…As shown in Fig. 2D, both heat shock and TBEV infection induced eIF2␣ phosphorylation in U2OS cells, most likely through protein kinase R (PKR) (19,33). To determine if TBEV prevents SG formation in response to heat shock, U2OS cells were electroporated with TNd/⌬ME_24ϫMS2.…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that these viruses inhibit SG formation by targeting TIA-1/TIAR either through the nonstructural protein NS3, which could be immunoprecipitated by both TIA-1 and TIAR, or through the viral 3=(Ϫ)SL RNA, which was earlier shown to bind TIAR and, to a lesser extent, TIA-1 (17). However, more recently, they reinterpreted their own data, this time looking at G3BP1 as a marker for SG, showing that natural WNV genotypes, such as Eg101, induced SG less efficiently than the lineage 2/1 chimeric WNV infectious clone W956IC, which produced high levels of early viral RNA (19). They proposed that induction of SG by WNV is closely linked to the availability of dsRNA to PKR signaling and that fast-replicating genotypes, such as W956IC, release more dsRNA from virus-induced vesicles, thus triggering the Ϫ/Ϫ and their control MEF WT were electroporated with TNd/⌬ME_C17_fluc_GAA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Formation of SG is PKR dependent in a number of virus-infected cell systems (49), including MV (19), hepatitis C virus (50), respiratory syncytial virus (51), and West Nile virus (52). Subcellular localization, kinetics of accumulation, and sensitivity to cycloheximide, a potent inhibitor of MV replication (40), suggest that the RNA responsible for the dsRNA signal observed in C KO mutant virus-infected cells is of viral and not of cellular origin.…”
Section: Discussionmentioning
confidence: 99%